Relação entre Covid-19, marcadores inflamatórios, intubação orotraqueal, respiração e voz - Feltrin, Thaís Dias (2022)
Objective: Is to verify the relation between the biological markers of inflammation Ddimers and C-Reactive Protein, Vital Capacity, Maximum Phonation Time, Vocal Performance Questionnaire and vocal fatigue index, length of stay and gender of people affected by COVID-19, and compare patients with and without orotracheal intubation. Methods: This is a cross-sectional and quantitative study. Inclusion criteria will be patients: male or female; ages between 20 and 65 years old; previous hospitalization with medical diagnosis of COVID-19 with or without orotracheal intubation. Exclusion criteria: Patients with reports or diagnosis of neurological, endocrinological, psychiatric, gastric or laryngeal or vocal alterations prior to COVID19; that did not pass the audiological screening; or declared themselves to be a smoker or a drinker. Were be carried out: a research of anthropometric data and assessments in medical records; anamnesis; hearing screening; collection of maximum phonation times; application of self-assessment instruments for performance and vocal fatigue. 42 cases of adults affected by COVID-19 who were hospitalized participated in the study, 22 (52,4%) were female and 20 (47,6%) were male, and 23 (54,8%) were group with orotracheal intubation (critical, mean age of 48,9 years) and 19 (45,2%) group without orotracheal intubation (severe, mean age of 49,9 years). Results: The results show that the group with orotracheal intubation needed to stay longer (25,8 days) versus the group without orotracheal intubation (10,7 days). Regarding the biological markers of inflammation, 22 (95,7%) of the group with orotracheal intubation presented altered results of D-dimers versus 14 (73,7) of the group without orotracheal intubation. Correlations between Maximum Phonation Time, vocal fatigue index and Vocal Performance Questionnaire are statistically significant. With results below expectations in the results of maximum phonation times of /a/, /s/ and /z/. 41 (97,6%) of the patients had an altered result in the vocal performance questionnaire. The group with orotracheal intubation 12 (52,2%) had vocal fatigue index alterations. About Vital Capacity in relation to sex and orotracheal intubation show that 32 (76,2%) are within the predicted values. Conclusion: Patients with orotracheal intubation have a higher hospitalization time with increased inflammatory markers, have vocal alterations with increased Vocal Performance Questionnaire and vocal fatigue index scores and lower Maximum Phonation Time in relation to normality, which can be explained by the persistent symptoms after the acute condition of the disease. The Vital Capacity was within the expected values due to the time between hospital discharge and the evaluations.